An analysis of employment participation and its determinants among older adults in Jambi Province, Indonesia - Riani, Eva; Wijayanto, Arie Wahyu; Rivai, Arham (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2024)
The older adult population in Jambi Province constituted 10.23% of the total population in 2023, categorizing it as an "aging population." This study aims to provide an overview of the employment participation of older adults in Jambi Province and to analyze the factors influencing their continued engagement in the labor force. The research employs descriptive and inferential analyses, utilizing binary logistic regression methods based on data from the National Labor Force Survey (Sakernas) conducted in October 2023 in Jambi Province. The findings reveal that the majority of the older adult population in Jambi Province remains actively employed, with 53.40% reporting work as their main activity. The working older adult population is predominantly characterized by individuals residing in rural areas, males, those with education levels up to junior high school or lower, individuals without physical limitations, married individuals, and heads of households—factors that significantly increase their likelihood of being employed in old age. The agricultural sector serves as the primary employer for the older adult workforce in Jambi, absorbing 69.64% of older adult workers, followed by the trade sector at 10.95%. Both sectors are characterized by their minimal reliance on formal educational qualifications, emphasizing physical capability over academic credentials.